(3eYQaI GdSff hGdBKGQs - (3GdHjgbj , CHh HcQ CMeO Hf GdMSjf Hf Ydj GdHjgbj GdNQGSGfj GdTGaYj, GdHjgbj,J (B458 (3g` s
(3ChdgG (B:s
(3jHJOF HChd GdcJGH s
(3BNQgG (B:s
(3hjfJgi HeG jSJOd Hg Ydi GNJUGU gPG Gdfgi HHYV GdUdhGJ Ohf HYV , ef HGH GdSGYI GdJi JcQg ajgG UdGI GdJWhY hGdChbGJ GdJi fgi Yf GdUdGI ajgG s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B116 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B206s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B107 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1739s
Keywords: (3GdMOjK h GdeUWdMs